2022
DOI: 10.2147/pgpm.s348170
|View full text |Cite
|
Sign up to set email alerts
|

GABRA1 and GABRB2 Polymorphisms are Associated with Propofol Susceptibility

Abstract: To explore the effect of gene polymorphisms of propofol GABA A receptor and metabolic enzyme on drug susceptibility during the induction period of general anesthesia. Patients and Methods: A total of 294 female patients aged 18-55 years, ASA I-II, who underwent hysteroscopy with intravenous general anesthesia, were included in the study. Anesthesia was induced by continuous intravenous infusion of propofol at 40 mg•kg −1 •h −1 . Infusion of propofol was ended when both the Modified Observer's Assessment of Awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Zeng et al found that GABRB2 rs3816596 and GABRA1 rs4263535 polymorphisms were associated with susceptibility to propofol sedation. ABRA1 rs1157122 and GABRB2 rs76774144 polymorphisms were associated with the degree of blood pressure drop after propofol infusion ( Zeng et al, 2022 ). A previous study by our group found an association between GABAA1 receptor SNP rs2279020 and sensitivity to BIS.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al found that GABRB2 rs3816596 and GABRA1 rs4263535 polymorphisms were associated with susceptibility to propofol sedation. ABRA1 rs1157122 and GABRB2 rs76774144 polymorphisms were associated with the degree of blood pressure drop after propofol infusion ( Zeng et al, 2022 ). A previous study by our group found an association between GABAA1 receptor SNP rs2279020 and sensitivity to BIS.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between the GABRA1 and GABRB2 genes and sensitivity to propofol were also determined. It has been shown that variants of GABRB2 rs3816596 and GABRA1 rs4263535 are associated with sensitivity to the sedative effect of propofol, and variants of GABRA1 rs1157122 and GABRB2 rs76774144 are associated with a lower degree of decrease in blood pressure after administration of propofol [20]. In addition, the CT/CC genotypes of GABRB1 rs4694846 were associated with heart rate instability, and the GG GABBR2 rs1167768 genotype was associated with greater instability of mean blood pressure values [21].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
“…Despite some positive correlation between specific genotypes and characteristics of propofol-induced anesthesia, the lack of reproducibility of the data limits the implementation of preoperative genetic screening to identify individuals requiring dose adjustment [20].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A single-nucleotide polymorphism can alter the function of a gene by affecting its expression or the structure of its coded protein. Relevant genes and some associated single-nucleotide polymorphisms involved in propofol pharmacodynamics and pharmacokinetics have been explored in hypothesis-driven candidate gene association studies focused on genes associated with GABA A receptors, [25][26][27] UGT1A9, CYP2B6, and CYP2C9, [28][29][30] but results have been inconsistent. The aim of this study was to identify genetic factors associated with dose requirements of propofol (mg • kg −1 • min −1 ) in a pseudosteady-state of general anesthesia (Entropy 40-60, GE Healthcare, Finland) by performing a genome-wide association study in a cohort of 1,000 women of Finnish origin undergoing breast cancer surgery.…”
Section: Genome-wide Study On Propofol Requirementsmentioning
confidence: 99%